Postnatal development of salivary phosphate, sodium and potassium secretion in calves - Muscher-Banse, Alexandra S.; Daenicke, Reinhard; Dänicke, Sven; Breves, Gerhard (Frontiers in Veterinary Science, 2023)
The transition of young lambs and calves from a non-ruminating to a ruminating animal include substantial, developmental changes to alter saliva production. Due to the simultaneous development of the forestomach system, the salivary glands must transfer more and more substances such as bicarbonate and phosphate (Pi), but also sodium (Na), into saliva in order to create and to maintain optimal environmental conditions for microbial metabolism. The objective of the present study was to characterize the effects of different dietary energy levels on the ability of the salivary glands to concentrate minerals in young ruminants in more detail during the first seven weeks of life. Blood and saliva samples were collected from twelve female calves of the German Holstein breed fed different levels of milk replacer. Plasma and saliva samples were collected over seven weeks postpartum and Na, Pi and potassium (K) concentrations were measured. Salivary Na and Pi concentrations (P < 0.001) increased as a function of time and were not affected by varying energy intake, while K concentration (P < 0.001) decreased over the developmental period and was also not affected by energy intake. This suggests that the ability to specifically concentrate minerals such as Na and Pi in saliva follows a genetic program in the salivary glands rather than being influenced by dietary factors such as energy intake in young ruminants.